SMALL TALK IN ROGER MICHELL’S MOVIE “NOTTING HILL” IN ENGLISH LITERATURE IN 2019 AT UNIVERSITAS NEGERI MAKASSAR - Suwina, Nuralifdah; Iskandar, Iskandar (Journal of English Literature and Linguistic Studies, 2023)
This article seeks and examines the types and impact of small talk in movies. The subject is Notting Hill, Roger Michell's. This article uses qualitative research techniques. Data is collected after watching the movie. The types of small talk are grouped using the theory of John Spacey (2018) and the impact that is in the film is analyzed by the ideas of Twenge, Jean M. & Campbell, W. (2009). The findings show that: (1) First, there are eight types of small talk in the movie "Notting Hill". Among them are: Conversation Opener, Close-Ended Questions, People, Social Categorization, Culture, Put Downs, and Professional. (2) Finally, there are two impacts that occur after small talk conversations from the main character in the movie "Notting Hill", which include positive and negative impacts. The results of this study prove that the Notting Hill movie contains several types of small talk, namely conversation starters, rhetorical questions, closed questions, people, social categorization, culture, boilerplate, putting, professional. From several types of small talk in the movie, it implies that there is an impact from every small talk conversation carried out by the main character in the movie.